Pengaruh Independensi, Self Efficacy, Etika Profesi dan Audit Tenure terhadap Audit Judgment dengan Spiritual Quotient sebagai Variabel Moderasi - Hairul Triwarti; Meinendy Hikmawardhani Dwi Putri (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2023)
This research aims to examine the effect of independence, self efficacy, professional ethics and audit tenure on audit judgment by using sprititual quotient as a moderating variable. This research is included in the type of quantitative research. The data collection method used is primary data with field survey methods. The technique used is by distributing questionnaires to 73 external auditor respondents who work in Public Accounting Firms in the DKI Jakarta area. The sampling technique used is non- probability sampling. The results of this study indicate that independence positive and significant effect on audit judgment, self efficacy positive and significant effect on audit judgment, professional ethics has no positive and significant effect on audit judgment, audit tenure positive and significant effect on audit judgment, spiritual quotient can strengthen the influence between independence against audit judgment, and spiritual quotient can strengthen the influence of professional ethics on audit judgment.